Differential influences of serum vitamin C on blood pressure based on age and sex in normotensive individuals - Huang, Rui; Song, Linhua; Zhao, Jingbo; Lei, Yuhua; Li, Tian (Frontiers in Nutrition, 2022)
Aim: Hypertension is among the most prevalent chronic diseases with diverse etiology, affecting over 1 billion people globally. Numerous studies have reported that vitamin C was inversely correlated with blood pressure and might have antihypertensive potential. However, the current research on the relationship between vitamin C and blood pressure was mainly carried out in hypertensive subjects with contradictory conclusions. The principal objective of this project was to investigate the relationship between vitamin C and blood pressure in normotensive adult subjects. Methods: A total of 2533 individuals aged 20 years and above were enrolled in the present study from the National Health and Nutrition Examination Survey (NHANES) 2017-2018. Outcome variables were systolic blood pressure(SBP) and diastolic blood pressure(DBP). Serum vitamin C was regarded as an independent variable. EmpowerStats software and R (version 3.4.3) were used to examine the association between vitamin C and SBP or DBP. Results: Vitamin C was reversely correlated with both SBP(β=-0.02, 95% CI:-0.04 to -0.01, p=0.0028) and DBP (β=-0.02, 95% CI:-0.03 to -0.01, p=0.0003) after adjusting all covariates. Sex, age, race/ethnicity might be major contributors affecting this reverse relationship. A U-shaped association between vitamin C and SBP in females and an inverted one between vitamin C and DBP in males were detected, respectively. We further calculated the inflection points at 90.3μmol/L for females and 40μmol/L for males. It is somewhat surprising that a reverse U-shaped distribution between vitamin C and SBP and DBP in people over 50 was detected, and the point of inflection of vitamin C were all located at 40μmol/L. Conclusions: Vitamin C was reversely correlated with both SBP and DBP in this cross-sectional analysis. However, a U-shaped relationship and an inverted one were also observed in certain people, which implied that, though vitamin C is considered a vital antioxidant, maintaining vitamin C at appropriate levels may be beneficial according to different populations.